2016
DOI: 10.1016/j.theriogenology.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Early epigenetic reprogramming in fertilized, cloned, and parthenogenetic embryos

Abstract: 18Despite ongoing research in a number of species, the efficiency of embryo production by of sperm fertilization through artificial activation -the parthenote-and will also be introduced. 25Altogether the objective of this review is to have a better understanding on the mechanisms 26 responsible for the resistance to reprogramming; not only because it could improve embryonic 27 development but also as it could benefit therapeutic reprogramming research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 99 publications
2
19
0
1
Order By: Relevance
“…Generally, incomplete DNA methylation reprogramming induced by SCNT can be due to the repressive factors present in donor cells [6]. Here, our results demonstrated that Dnmt1s in donor cells serves as a critical barrier for ZGA and genomic methylation reprogramming, leading to the developmental arrest of SCNT embryos, and removal of this barrier by siRNA enhances DNA methylation reprogramming, allows the efficient activation of genes required for embryonic development, and thus improves the SCNT efficiency (Figure 6).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Generally, incomplete DNA methylation reprogramming induced by SCNT can be due to the repressive factors present in donor cells [6]. Here, our results demonstrated that Dnmt1s in donor cells serves as a critical barrier for ZGA and genomic methylation reprogramming, leading to the developmental arrest of SCNT embryos, and removal of this barrier by siRNA enhances DNA methylation reprogramming, allows the efficient activation of genes required for embryonic development, and thus improves the SCNT efficiency (Figure 6).…”
Section: Discussionsupporting
confidence: 52%
“…However, to date, the cloning efficiency remains low, limiting SCNT-associated research and application [46]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniparental embryos are an effective tool to explore genetic effects on the process of maternal and paternal genomic imprinting, as well as the contribution of the maternal and paternal genome in early embryonic development (Latham, Kutyna & Wang, 1999; Kono et al, 2004; Gebert et al, 2009; Sepulveda-Rincon et al, 2016; Ogawa et al, 2009). Some studies report that the addition of granulocyte colony-stimulating factor and valproic acid, AY9944A-7 and histone deacetylase inhibitor in the IVM medium improve the viability of parthenogenetic embryos in porcine (Cai et al, 2015; Huang et al, 2015), sheep (Hao et al, 2015) and androgenetic embryos in bovine (Zhang et al, 2014), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This rate greatly limits the widespread application of nuclear transfer technology. The low developmental efficiency of SCNT embryos is mainly attributed to the incomplete reprogramming of the donor cell’s nuclear genome during preimplantation embryo development [5]. …”
Section: Introductionmentioning
confidence: 99%